2008
DOI: 10.1007/bf03086117
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced versus non-enhanced three-dimensional echocardiography of left ventricular volumes

Abstract: Contrast-enhanced versus non-enhanced three-dimensional echocardiography of left ventricular volumesBackground. In three-dimensional echocardiography (3DE), individual endocardial trabeculae are not clearly visible necessitating left ventricular (LV) volumes to be measured by tracing the innermost endocardial contour. Ultrasound contrast agents aim to improve endocardial definition, but may delineate the outermost endocardial contour by filling up intertrabecular space. Although measurement reproducibility may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In most publications, 3DTTE has been shown to slightly underestimate both end-diastolic (EDVs) and end-systolic volumes (ESVs). Although these findings are generally consistent with the literature, one caveat is that only two of the included studies used echocardiographic contrast [25,26], which has been shown to improve accuracy of RT3DTTE volumes and ejection fraction compared with a CMR standard [25,27,28]. Among the few studies that did not exclude patients for poor image quality, the negative volume biases were slightly larger: À28.8 AE 38 ml, À17.9 AE 34 ml, and þ0.3 AE 15.5% for EDV, ESV, and ejection fraction, respectively.…”
Section: Quantification Of Left Ventricular Volumes and Ejection Fracsupporting
confidence: 86%
“…In most publications, 3DTTE has been shown to slightly underestimate both end-diastolic (EDVs) and end-systolic volumes (ESVs). Although these findings are generally consistent with the literature, one caveat is that only two of the included studies used echocardiographic contrast [25,26], which has been shown to improve accuracy of RT3DTTE volumes and ejection fraction compared with a CMR standard [25,27,28]. Among the few studies that did not exclude patients for poor image quality, the negative volume biases were slightly larger: À28.8 AE 38 ml, À17.9 AE 34 ml, and þ0.3 AE 15.5% for EDV, ESV, and ejection fraction, respectively.…”
Section: Quantification Of Left Ventricular Volumes and Ejection Fracsupporting
confidence: 86%
“…Use of contrast agents was not included in the original study because previous studies have shown that it may lead to overestimation of the volumes and it sometimes suppressed cardiac function in the pigs in our previous experiments. 16 The findings of this study should be validated in humans before applied to clinical practice as discussed above, especially in critically ill patients where the acoustic imaging is limited in a different way than pigs.…”
Section: Discussionmentioning
confidence: 90%
“…Though its contribution is considered relatively small because the measurements were performed immediately after creating myocardial infarction, it might have contributed partially to the overestimation of SV by echocardiography compared with TDM. Use of contrast agents was not included in the original study because previous studies have shown that it may lead to overestimation of the volumes and it sometimes suppressed cardiac function in the pigs in our previous experiments 16 . The findings of this study should be validated in humans before applied to clinical practice as discussed above, especially in critically ill patients where the acoustic imaging is limited in a different way than pigs.…”
Section: Discussionmentioning
confidence: 99%